Trace-element analysis of mineral grains in Ryugu rock fragment sections by synchrotron-based confocal X-ray fluorescence - Benjamin Bazi; Pieter Tack; Miles Lindner; Bart Vekemans; Ella De Pauw; Beverley Tkalcec; Frank E. Brenker; Jan Garrevoet; Gerald Falkenberg; Hikaru Yabuta; Hisayoshi Yurimoto; Tomoki Nakamura; et al. (figshare, 2022)
Abstract A fundamental parameter-based quantification scheme for confocal XRF was applied to sub-micron synchrotron radiation X-ray fluorescence (SR-XRF) data obtained at the beamline P06 of the Deutsches Elektronen-Synchrotron (DESY, Hamburg, Germany) from two sections C0033-01 and C0033-04 that were wet cut from rock fragment C0033 collected from Cb-type asteroid (162173) Ryugu by JAXA’s Hayabusa2 mission. Trace-element quantifications show that C0033 bulk matrix is CI-like, whereas individual mineral grains (i.e., magnetite, pyrrhotite, dolomite, apatite and breunnerite) show, depending on the respective phase, minor to strong deviations. The non-destructive nature of SR-XRF coupled with a new PyMca (a Python toolkit for XRF data analysis)-based quantification approach, performed in parallel with the synchrotron experiments, proves to be an attractive tool for the initial analysis of samples from return missions, such as Hayabusa2 and OSIRIS-REx, the latter returning material from a B-type asteroid (101955) Bennu in 2023. Graphical Abstract
Keywords: Biophysics; Space Science; 29999 Physical Sciences not elsewhere classified; Medicine; Physiology; Biotechnology; 39999 Chemical Sciences not elsewhere classified; Marine Biology; Plant Biology